FOSTERING STUDENTS’ CONCEPT MASTERY THROUGH STEM-ENGINEERING DESIGN PROCESS IN THERMAL ENERGY AND HEAT TRANSFER TOPIC - Hasanah Purnama, Aisyah Nurul; Winarno, Nanang; Prima, Eka Cahya; Ahmad, Nur Jahan (INSECTA: Integrative Science Education and Teaching Activity Journal, 2023)
This study aims to investigate the effect of STEM-EDP on students' concept mastery in thermal energy and heat transfer topic. Employing a quasi-experimental design, the study incorporates pretest and posttest across both an experiment class and a control class. The Experimental class using the STEM-EDP while control class using the conventional as the learning approach. The study encompasses 35 seventh-grade students for each class from one of Junior High School in Bandung, Indonesia. The instruments include an objective test that spans cognitive levels from C1 to C5 based on the Bloom Taxonomy. The result shows that there are significant differences between experimental and control class in both concept mastery. This is evident from the p-values of 0.03 in independent t-test results for concept mastery. In terms of improvement, the N-Gain of experiment class for concept mastery stands at 0.22, characterizing a low improvement. While, the N-gain of control class is 0.08, also characterizing as a low improvement. In light of these outcomes, it is reasonable to consider STEM-EDP as a valuable pedagogical approach within Junior High School in fostering a deeper understanding of scientific concepts especially in thermal energy and heat transfer topic.